2001
DOI: 10.1046/j.1472-765x.2001.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal methanogenesis as influenced by individual fatty acids supplemented to complete ruminant diets

Abstract: The objective of the present study was to investigate the effects of seven different pure fatty acids on rumen fermentation using the rumen simulation technique (RUSITEC). The fatty acids were supplied to a complete ruminant diet at a proportion of 50 g x kg(-1) dietary dry matter and compared with an unsupplemented control. Methane release and methanogenic counts were suppressed by the fatty acids C12 : 0, C14 : 0 and C18 : 2 whereas C8 : 0, C10 : 0, C16 : 0 and C18 : 0 showed no corresponding effects. Apart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 19 publications
7
84
1
1
Order By: Relevance
“…Combination of coconut oil with sunflower oil can decrease protozoal numbers without impact on bacterial population. This result was in agreement with Dohme et al (2001) who found that both myristic acid (C12:0) and lauric acid (C14:0), rich in coconut oil, and linoleic acid (C18:2) or linolenic acid (18:3) which rich in sunflower oil can reduce population of protozoa in in vitro fermentation. Moreover, Odongo et al (2007) found that dietary supplementation with myristic acid reduced methane production from dairy cows.…”
Section: Discussionsupporting
confidence: 93%
“…Combination of coconut oil with sunflower oil can decrease protozoal numbers without impact on bacterial population. This result was in agreement with Dohme et al (2001) who found that both myristic acid (C12:0) and lauric acid (C14:0), rich in coconut oil, and linoleic acid (C18:2) or linolenic acid (18:3) which rich in sunflower oil can reduce population of protozoa in in vitro fermentation. Moreover, Odongo et al (2007) found that dietary supplementation with myristic acid reduced methane production from dairy cows.…”
Section: Discussionsupporting
confidence: 93%
“…This is in contrast to Palmquist (1991) finding no adverse effect of non-esterified FA applied to dairy cows on DM and fibre digestibilities compared to other fat sources. Although a negative effect of MCFA on gram positive rumen bacteria cannot be excluded (Galbraith et al, 1971), in vitro counts of total rumen bacteria and total VFA concentration were not different between an unsupplemented diet and diets supplemented either with C12 : 0, C14 : 0 or C18 : 0 (Dohme et al, 2001). In the same study, C12 : 0 significantly reduced ruminal degradation of NDF which is in contrast to the present lack of significant effect on total tract digestibility of CF and NDF.…”
Section: Effect Of Lauric Myristic and Stearic Acid On The Utilizatimentioning
confidence: 49%
“…Even dietary coconut oil proportions as high as 70 g/kg had only insignificant effects on fibre digestion and heat production of adult sheep (Machmu¨ller and Kreuzer, 1999). As these studies showed, coconut oil reduced methanogenesis in ruminants, and C12 : 0 and C14 : 0 have been identified in vitro as the FA responsible for this favourable effect (Dohme et al, 2001) although they differ in their mode of action . The MCFA are also known to be predominantly used for energetic purpose in metabolism of rodents (Lavau and Hashim, 1978).…”
Section: Introductionmentioning
confidence: 80%
“…However, it was found that supplementation of 7% coconut oil with garlic powder (50 or 100 g day −1 ) tended to increase total DM intake when compared with 7% coconut oil supplementation. This tendency to reduce DM intake was not surprising because coconut oil has been shown to interact with dietary fiber in the rumen to depress fiber degradability (Dohme et al, 2001). Rice straw intake per day had shown similar results with total DM intake result.…”
Section: Feed Intake and Apparent Digestibility Of Nutrientsmentioning
confidence: 60%